2015
DOI: 10.1371/journal.pone.0137401
|View full text |Cite
|
Sign up to set email alerts
|

Cloacal Microbiome Structure in a Long-Distance Migratory Bird Assessed Using Deep 16sRNA Pyrosequencing

Abstract: Effects of vertebrate-associated microbiota on physiology and health are of significant interest in current biological research. Most previous studies have focused on host-microbiota interactions in captive-bred mammalian models. These interactions and their outcomes are still relatively understudied, however, in wild populations and non-mammalian taxa. Using deep pyrosequencing, we described the cloacal microbiome (CM) composition in free living barn swallows Hirundo rustica, a long-distance migratory passeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
84
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 80 publications
11
84
3
Order By: Relevance
“…The phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes dominated barn swallow CMs, consistently with the results on populations from the Czech Republic, which are~580 km far from our study area, where a high abundance of the phylum Tenericutes was also reported (Kreisinger et al 2015(Kreisinger et al , 2017. Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes dominated barn swallow CMs, consistently with the results on populations from the Czech Republic, which are~580 km far from our study area, where a high abundance of the phylum Tenericutes was also reported (Kreisinger et al 2015(Kreisinger et al , 2017. Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015). A more detailed description of the bacterial community at a lower taxonomic level showed that the most abundant genera differed from those observed in previous studies: the genera Ralstonia, Pseudomonas, Aeribacillus, and Arenimonas were abundant in our samples, while they were not found in the two previous studies in the Czech Republic (Kreisinger et al 2015(Kreisinger et al , 2017. Ralstonia spp.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations